The effect of robot's behavior vs. appearance on communication with humans - Eunil Park; Hwayeon Kong; Hyeong-taek Lim; Jongsik Lee; Sangseok You; del Pobil, A. P. (2011 6th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2011)
This study explores the effect of the robot's appearance vs. behavior (voice and gestures) on the way it is perceived as a machine-like instead of a human-like robot. A between-subjects experiment with four conditions was conducted. Results suggest that both the robot's behavior and appearance are important but, if they are contradictory, the robot's behavior is more powerful than the robot's appearance in the perception of the robot as more machine-like or human-like.